PENGETAHUAN DAN SIKAP KESIAPSIAGAAN MASYARAKAT TERHADAP BENCANA TANAH LONGSOR DI DESA GUNUNG TUA KECAMATAN TANAH PINEM KABUPATEN DAIRI - Heriaty Berutu; Herlina Evi Yanti Manik (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2023)
Residents and settlements in Gunung Tua District, Tanah Pinem, Dairi Regency have a high risk of landslides. If an area has a high vulnerability to landslides, it is necessary for the community to have knowledge and attitudes in order to increase community preparedness in dealing with landslide disasters. The purpose of this study is to analyze disaster knowledge and preparedness attitudes as well as preparedness for land slide disasters. The method used in this research is quantitative. The sample in this study is the community of 90 respondents taken from each village. Data collection techniques using questionnaires / questionnaires and documentation studies. The data analysis technique is a percentage analysis technique. Based on the results of the study, it was found that of the 90 respondents, the majority of respondents had sufficient knowledge, 59 respondents (65.6%), and a minority with less knowledge, namely 6 respondents (6.7%). The preparedness attitude of the majority of respondents has sufficient attitude as many as 66 respondents (73.3%), and the minority attitude is lacking, namely 6 respondents (6.7%). This research is useful for the community, local government, and educational practitioners and scientific practitioners in the field of natural landslide disasters to be developed and perfected in further research related to knowledge and attitudes towards preparedness for landslide disasters.